Pengalaman Self Directed Learning Mahasiswa dalam Project Based Learning - 'Aini, Zahratul; Adri, Zakwan (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to see an overview of students' self-directed learning experiences when conducting project-based learning. This study uses a qualitative method with a phenomenological approach. Participants in this study are students who are or have participated in project-based learning. Data analysis was carried out using the Interpretative Phenomenological Analysis (IPA) method to understand students' in-depth experience in managing self-directed learning. The validity of the research is maintained through triangulation of data sources and confirmation of results to participants The research results show that students who have good self-directed learning skills can overcome various challenges in project based learning such as problems in team collaboration and time management. In addition, the self-evaluation carried out by students during the learning process helps them improve critical thinking skills, resource management and independence. Intrinsic motivation factors and external support play an important role in supporting the success of self-directed learning in project based learning. This research concludes that self-directed learning plays a significant role in increasing the effectiveness of studenjt learning in project based learning, both in terms of academic results and life skills development